2019
DOI: 10.1128/mcb.00410-18
|View full text |Cite
|
Sign up to set email alerts
|

A Feedback Loop between MicroRNA 155 (miR-155), Programmed Cell Death 4, and Activation Protein 1 Modulates the Expression of miR-155 and Tumorigenesis in Tongue Cancer

Abstract: MicroRNA 155 (miR-155) is an oncomir, generated as a noncoding RNA from the BIC gene whose promoter activity is mainly controlled via activation protein 1 (AP-1) and NF-κB transcription factors. We found that the expression levels of miR-155 and programmed cell death 4 (Pdcd4) exhibit inverse relationships in tongue cancer cells (SAS and AWL) and tumor tissues compared to their relationships in normal FBM cells and normal tongue tissues, respectively. In silico and in vitro studies with the 3′ untranslated reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Although the miRNAs were selected because of their modulation of inflammation, several of them exhibited other, perhaps independent, actions related to tumor promotion and progression. In fact, several molecules listed have been classified as oncomiRs, such as miR-21, miR-23a, miR-29, miR-106b, miR-125b, miR-155, and miR-182 [ 316 , 362 , 363 , 364 ].…”
Section: Modulation Of the Network By Noncoding Rnas An Emergingmentioning
confidence: 99%
“…Although the miRNAs were selected because of their modulation of inflammation, several of them exhibited other, perhaps independent, actions related to tumor promotion and progression. In fact, several molecules listed have been classified as oncomiRs, such as miR-21, miR-23a, miR-29, miR-106b, miR-125b, miR-155, and miR-182 [ 316 , 362 , 363 , 364 ].…”
Section: Modulation Of the Network By Noncoding Rnas An Emergingmentioning
confidence: 99%
“…Elevated expression of hypoxia-inducible factor-1 α (HIF-1 α ) increases trophoblastic apoptosis by regulating FOXO3a [ 35 ]. Furthermore, the correlation of miR-155 and FOXO3 was previously reported in tumors as follows: expression of miR-155 is upregulated in tumors and acts as an oncogene in cancer [ 36 , 37 ], while expression of FOXO3 is downregulated and can inhibit the development of tumors [ 38 , 39 ]. A recent study by Cai et al [ 40 ] not only showed that FOXO3 overexpression promotes trophoblast cell proliferation, migration, invasion, and inhibits apoptosis but also demonstrated that the miR-155/FOXO3 axis is involved in the suppressive effects of Baicalin on the progression of PE.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, expression of miR-155 is regulated by a feedback circuit between Pdcd4, AP-1, and miR-155. Up-regulation of miR-155 results in progression of this type of cancer ( 78 ). Table 6 shows the interaction between miRNAs and PDCD in head and neck cancers.…”
Section: Mirnas and Pdcdmentioning
confidence: 99%